Biophilic Design Effects on Kindergarten Interior: Nature Integration Enhance Learning Environment - Al-Radaideh, Bassam N.; Harafshe, Muna I.; Al-Shbool, Omar A.; Obeidat, Asem M. (Journal of Ecohumanism, 2024)
This study aimed to ascertain the level of contribution that integrating nature (biophilia) in interior design has on kindergartens. The Descriptive method was preferred because it best suited the nature and objectives of the study. A sample of 30 educational institutions (kindergartens) in all kingdom regions: North Region, Central Region and South Region were used. The regions had 5 public and 5 private children’s homes each as part of the sample. The data collection instrument for this study was a questionnaire whose areas were divided into two; contribution of integrating nature (biophilia) in interior design kindergartens with seven items and role played by nature (biophilia) towards comfort and health among children within kindergarten containing six items.”The findings revealed significant statistical differences in the extent to which nature (biophilia) was integrated into the interior design of kindergartens, particularly in private ones. By connecting with nature, relaxation and focus can be improved as well as emotional stability for both children and teachers. It therefore suggests that diverse, colorful indoor and outdoor spaces provided with trees, plants and other natural areas where children can play should be made available.